Knowledge brokers at the interface of environmental science and policy: A review of knowledge and research needs - C. Cvitanovic; DB Karcher; J. Breen; N. Badullovich; P. Cairney; R. Dalla Pozza; J. Duggan; S. Hoffmann; R. Kelly; AM Meadow; S. Posner (Environmental Science & Policy, 2025)

Compositional effects in the liquid Fe–Ni–C system at high pressure - Esther S. Posner; Gerd Steinle-Neumann (Physics and Chemistry of Minerals, 2022)
We performed molecular dynamics simulations based on density functional theory to systematically investigate the Fe–Ni–C system including (1) pure Fe and Ni; (2) binary Fe–Ni, Fe–C, and Ni–C; and (3) ternary Fe–Ni–C liquid compositions at 3000 K and three simulation volumes corresponding to pressure ( P ) up to 83 GPa. Liquid structural properties, including coordination numbers, are analyzed using partial radial distribution functions. Self-diffusion coefficients are determined based on the atomic trajectories and the asymptotic slope of the time-dependent mean-square displacement. The results indicate that the average interatomic distance between two Fe atoms ( r Fe–Fe ) decreases with P and is sensitive to Ni ( X Ni ) and C ( X C ) concentration, although the effects are opposite: r Fe–Fe decreases with increasing X Ni , but increases with increasing X C . Average r Fe–C and r Ni–C values also decrease with increasing X Ni and generally remain constant between the two lowest P points, corresponding to a coordination change of carbon from ~ 6.8 to ~ 8.0, and then decrease with additional P once the coordination change is complete. Carbon clustering occurs in both binary (especially Ni–C) and ternary compositions with short-range r C-C values (~ 1.29 to ~ 1.57 Å), typical for r C-C in diamond and graphite. The self-diffusion results are generally consistent with high- P diffusion data extrapolated from experiments conducted at lower temperature ( T ). A subset of additional simulations was conducted at 1675 and 2350 K to estimate the effect of T on diffusion, yielding an activation enthalpy of ~ 53 kJ/mol and activation volume of ~ 0.5 cm 3 /mol.

Repetitive Head Impact Exposure in College Football Following an NCAA Rule Change to Eliminate Two-A-Day Preseason Practices: A Study from the NCAA-DoD CARE Consortium - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Stefan Duma; Jason P. Mihalik; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Megan N. Houston; Jonathan Jackson; et al. (Annals of Biomedical Engineering, 2019)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Interdisciplinary Oncology Education: a National Survey of Trainees and Program Directors in the United States - Adil S. Akthar; Christopher D. Hellekson; Sabha Ganai; Olwen M. Hahn; Ronald J. Maggiore; Ezra E. Cohen; Mitchell C. Posner; Steven J. Chmura; Andrew R. Howard; Daniel W. Golden (Journal of Cancer Education, 2018)

High-pressure single-crystal X-ray diffraction study of jadeite and kosmochlor - Esther S. Posner; Przemyslaw Dera; Robert T. Downs; John D. Lazarz; Peyton Irmen (Physics and Chemistry of Minerals, 2014)